Avibacterium paragallinarum and Gallibacterium spp. coinfection in laying hens with sinusitis and rhinitis - Priscilla M.C. Rocha; Maria E.G. Barros; Jéssica T. Bandeira; Renato S.M.M. Morais; Juliana F.V. Braga; Francisco A.L. Souza; Fábio S. Mendonça; Joaquim Evêncio-Neto (Pesquisa Veterinária Brasileira)
ABSTRACT: Respiratory diseases are responsible for economic losses in the poultry sector. The occurrence of coinfections can aggravate the severity of clinical signs and lesions, such as coinfection with Avibacterium paragallinarum and Gallibacterium spp. The aim of this study is to describe the epidemiological, clinical and pathological aspects of an outbreak of respiratory disease in laying hens caused by a coinfection by A. paragallinarum and Gallibacterium spp. in the state of Sergipe, northeastern Brazil. High morbidity and mortality were observed, accompanied by apathy, anorexia, serous nasal discharge and a decrease in egg production (approximately 10%). Five laying hens were selected for general clinical examination and euthanized. Samples of nasal turbinates, infraorbital sinuses, trachea, liver and spleen were collected, fixed in 10% buffered formalin and routinely processed for histopathology. For the microbiological examination, the whole heads of the birds were collected, packed in Nasco® plastic bags, stored at -8°C then sent to a private laboratory for bacterial isolation on Petri dishes containing blood agar and incubated at 37°C in microaerophilic. Grossly, there was a bilateral increase of periorbital volume with complete obstruction of nasal turbinates due to the presence of caseous exudate. Microscopically, there was marked diffuse chronic necrocaseous and granulomatous rhinitis, marked diffuse chronic granulomatous and heterophilic necrotizing sinusitis, focally extense lymphohistiocytic and heterophilic tracheitis with epithelial hyperplasia, loss of cilia and atrophy of mucous glands. In the microbiological examination, A. paragallinarum and Gallibacterium spp. were identified, and it was concluded that these agents were responsible for the outbreak of rhinitis and sinusitis in the studied birds.